REALbasic - Anderson, Al.; Safari eBooks ([S.l.] : Virtual Training Co., 2003)
"REALbasic is an object-oriented programming language that is based on the BASIC language. It was developed by REAL Software. REALbasic is a cross-platform development vehicle. You can use REALbasic to create software for Windows, Macintosh and Linux from a single set of source code! VTC author Al Anderson guides you through the basics of setting up, designing and creating your first REALbasic program in this tutorial. To begin learning simply click the links."--Resource description page.
Date of publication from resource description page (viewed June 11, 2012).
Title, publisher, and author name from title screen.
Presenter, Al Anderson.
Keywords: REALbasic (Computer program language); Object-oriented programming (Computer science); BASIC (Computer program language); Electronic books